ORGANIZATIONAL CULTURE AT UNIVERSITIES: COMPARATIVE STUDY OF INTERNATIONAL PRACTICES (EDUCATION IN THE 21ST CENTURY, 2023)
Organizational culture for effective functioning of universities is one of the main prerequisites for ensuring a good environment. Although organizational culture is informal in nature, it can serve as a crucial factor in managerial decision-making and quality enhancement of processes. The current article explores four main types of organizational culture (clan, adhocracy, hierarchy and market cultures) [4] at international higher education institutions (HEIs). By comparing and analyzing the professional literature, it becomes evident that at international HEIs clan organizational culture is more vivid. Even if other types of organizational culture are mostly adopted by universities, they still strive to have a clan organizational culture. Clan culture fosters a sense of cohesiveness and connectedness among members, and, respectively, enhances their ownership and organizational commitment. In a clan culture, everyone collaborates for the betterment of the organization, making it easier to make collective decisions that are best for the group.
Keywords: organizational culture at universities; organizational culture types; organizational culture at international universities